Lepra reactions in new leprosy cases at diagnosis: a study of 50 Pakistani patients - Rabia Ghafoor; Muhammad Irfan Anwar; Mutaher Zia (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the occurrence and characteristics of the two types of lepra reactions, in new leprosy cases at initial diagnosis, in a Pakistani population. Methods: This retrospective descriptive study was done at MALC Karachi .All new leprosy cases who were registered at MALC during a two-and-a-half year period were enrolled. Their medical records were checked and selected all cases who had presented with a lepra reaction, at initial diagnosis. A total of 50 such cases were identified. Data was then collected from their medical histories, physical examination records and laboratory investigation reports. Results: Out of the total 50 cases in this study, 2 (4%) were children and 48 (96%) were adults. Male-female ratio was 4.6:1. 30 (60%) cases presented with a type 1 reaction and 20 (40%) with type 2. 30 (60%) cases were classified as borderline lepromatous (BL). Among these 17 (57%) had a type 2 reaction. Inflamed plaques were the main feature, in 27 (90%) cases of type 1. Crops of painful, erythematous nodules were seen in 19/20; 95% cases of type 2. Ulnar nerves were the most commonly enlarged nerves, in those with type 1 (73%) and common peroneal in type 2 (65%). Conclusion: Lepra reactions can be a presenting feature in a significant number of new leprosy cases, at initial diagnosis. Early recognition and management of these reactions can help prevent disease transmission, lifelong deformities and disabilities. Keywords: Leprosy, Lepra reactions, type 1 (reversal) reaction, type 2 erythema nodosum leprosum (ENL) reaction. Continuous..